DISEMINASI PENGETAHUAN TENTANG TOKOH KI NARTOSABDHO MELALUI EVENT FESTIVAL SEABAD NADA DAN WARISAN KI NARTOSABDHO KEPADA PEGIAT SENI MAHASISWA DI KOTA SEMARANG SEBAGAI SOCIAL MEDIA SPECIALIST & COPYWRITER DAN DATA INSIGHT EXECUTIVE - Sharleen Uliartha Hutapea; S. Rouli Manalu (Interaksi Online, 2026)
The low level of understanding among young art practitioners regarding the figure of Ki Nartosabdho poses a challenge to the preservation of Javanese arts in Semarang. Although interest in Javanese culture remains relatively high, knowledge about the figure, works, and contributions of Ki Nartosabdho is still limited. Therefore, this project aims to enhance the knowledge and understanding of young art practitioners through the implementation of a cultural festival titled Festival Seabad Nada dan Warisan Ki Nartosabdho. This project applies the concept of Integrated Marketing Communication (IMC), which integrates communication strategies through advertising, public relations and publicity, as well as events and experiences. The method used is an implementation-based approach through the design and execution of a cultural festival involving student art organizations (UKM) in Semarang. The festival activities include art performances, multimedia exhibitions, cultural discussions, and collaborative showcases. In its implementation, the author took roles as Social Media Specialist and Copywriter, Data Insight Executive, as well as Finance Manager and Administration Manager. The results indicate an increase in youth engagement in art activities themed around Ki Nartosabdho, as well as an improvement in audience understanding of the figure’s works and contributions. The festival serves as a medium for cultural knowledge dissemination and a collaborative platform for student art communities in Semarang.